Prevalence, and health- and sociodemographic associations for visits to traditional and complementary medical providers in the seventh survey of the Tromsø study - Agnete E. Kristoffersen; Ann Ragnhild Broderstad; Frauke Musial; Trine Stub (BMC, 2019)
Abstract Background Patient-centered culturally sensitive health care (PC-CSHC) has emerged as a primary approach to health care. This care focuses on the cultural diversity of the patients rather than the views of the health care professionals. PC-CSHC enables the patient to feel comfortable, respected, and trusted in the health care delivery process. As users of traditional and complementary medicine (T&CM) rarely inform their conventional health care providers of such use, the providers need to identify the users of T&CM themselves to avoid negative interaction with conventional medicine and to be able to provide them with PC-CSHC. Since the patterns of traditional medicine (TM) use are different to those of complementary medicine (CM), the aim of this study was to investigate the prevalence, and the health- and sociodemographic associations for visits to TM- and CM providers in an urban population. Method The data were collected through two self-administrated questionnaires from the seventh survey of the Tromsø Study, a population-based cohort study conducted in 2015-2016. All inhabitants of Tromsø aged 40 or above were invited (n = 32,591) and n = 21,083 accepted the invitation (response rate 65%). Pearson chi-square tests and one-way ANOVA tests were used to describe differences between the groups whereas binary logistic regressions were used for adjusted values. Results The results revealed that 2.5% of the participants had seen a TM provider, 8.5% had seen a CM provider whereas 1% had visited both a TM and a CM provider during a 12-month period. TM users tended to be older, claim that religion was more important to them, have poorer economy and health, and have lower education compared to CM users. We found that more than 90% of the participants visiting T&CM providers also used conventional medicine. Conclusion A considerable number of the participants in this study employed parallel health care modalities including visits to conventional, traditional, and complementary medicine providers. To offer patient-centered culturally sensitive health care that is tailored to the patients' treatment philosophy and spiritual needs, conventional health care providers need knowledge about, and respect for their patients' use of parallel health care systems.